The Impact of Integrating the Flipped Classroom Strategy with Think-Aloud Techniques in Mathematics Instruction on Enhancing Deep Understanding and Self-Efficacy Among Female University Students - Helal, Osama H.; Alibraheim, Essa A.; Youssef, Nasser H.; AlOhali, Manal I.; Almuaddi, Saad M.; Barakat, Afaf M. (Journal of Posthumanism, 2025)
This study aimed to examine the impact of integrating the flipped classroom strategy and think-aloud strategy on developing deep understanding and self-efficacy in mathematics among preparatory-year female students in Saudi Arabia. A quasi-experimental design was employed with a sample of 80 students enrolled in a general mathematics course. Participants were randomly assigned to two equivalent groups: the experimental group (40 students), who studied the course using the integrated flipped classroom and think-aloud strategies, and the control group (40 students), who studied the same course using traditional methods. The study utilized a deep understanding test in mathematics and a self-efficacy scale in mathematics as data collection instruments. Both instruments were administered to the two groups before and after the treatment, and the collected data were analyzed statistically. The results revealed a statistically significant difference in favor of the experimental group in the post-test scores of both the deep understanding test and the self-efficacy scale, indicating a high effect size and strong effectiveness. The study recommended that university faculty members adopt modern teaching strategies, particularly those integrating multiple instructional approaches such as the flipped classroom and think-aloud strategies. It also emphasized the importance of training faculty members on these methods to enhance various aspects of teaching and learning at the university level.